Evaluation of adverse drug reactions in patients receiving second-line therapy for multidrug-resistant tuberculosis - Sri Rangan P. B., Venkat; Sikander, Sabia; Darga, Mohammed R.; Alam, Shameema; Razvi, Syed S. A. H.; Jyothi, Byru (International Journal of Research in Medical Sciences, 2026)
Background: Multidrug-resistant tuberculosis (MDR-TB) poses a major challenge to tuberculosis control, particularly in high-burden countries like India. Treatment of MDR-TB requires prolonged use of second-line anti-tubercular drugs, which are frequently associated with adverse drug reactions. These adverse drug reactions (ADRs) can adversely affect treatment adherence, increase morbidity, and compromise overall treatment outcomes, highlighting the importance of systematic pharmacovigilance. Aim of the study was to analyze the pattern, frequency, and spectrum of adverse drug reactions associated with anti-tubercular drugs in patients with MDR-TB. Methods: A retrospective descriptive study was conducted among 178 adult MDR-TB patients treated at a tertiary care center between January and December 2024. Patient records were reviewed for demographic details, clinical characteristics, treatment regimens, and reported ADRs. ADRs were categorized by organ system involvement, assessed for causality using the Naranjo scale, and graded for severity using the Hartwig and Siegel scale. Data were analyzed using descriptive statistics. Results: MDR-TB was more common among males and individuals aged ≤40 years. Endocrine ADRs (18.3%) were the most frequently reported, followed by otic toxicity (14.6%), musculoskeletal complaints (13.5%), and gastrointestinal disturbances (11.4%). Hepatic, dermatological, neurological, and renal ADRs were also observed. Conclusions: ADRs are common among MDR-TB patients receiving second-line therapy. Early detection, regular monitoring, and strengthened pharmacovigilance are essential to improve treatment adherence and outcomes.